Impunity and transitional justice in Indonesia: Aksi Kamisan’s circular time - Drexler, Elizabeth F. (International journal of transitional justice, 2022)
This article positions the Indonesian weekly Thursday silent protests by victims’ families, Aksi Kamisan, as a space of and beyond transitional justice. Analysing Kamisan as repeated, embodied creative acts that reset perceptions, possibilities and imaginations about social belonging, political subjectivity and national identity discloses how authoritarian era affective forces undermine transitional justice and demonstrates the power of alternative temporalities in coming to terms with past violence. ‘Circular time’ brings past and present injustice into the same frame as consistent action extending into the future. Circular time highlights how the time of waiting, uncertainty and lack of justice extends backward and forward connecting past, present and future in the repetition of impunity, and creates community and the space to imagine just futures. Circular time is created by repeated action against impunity in the present and celebrating the perseverance, consistency and agency of victims. Circular time resists the imposition of temporal linearity. Art performed at Kamisan and the act of standing in solidarity engages communities and audiences in a realm of politics and national belonging that is not possible in formal institutions. Over time, these repeated, temporary, inclusive actions can counter still resonant authoritarian era propaganda.